2015
DOI: 10.1002/cb.1567
|View full text |Cite
|
Sign up to set email alerts
|

What to diffuse in a gender‐specific store? The effect of male and female perfumes on customer value and behaviour

Abstract: Sensory marketing can be an efficient way to involve consumers in the store environment. Diffusing a pleasant ambient scent that matches with the store setting is often used to create pleasant shopping experiences. The aim of this study is to extend scent marketing research: (i) by examining the effect of pleasant ambient scent on the different dimensions of customer value; and (ii) by exploring whether product-scent incongruity can have a positive effect on consumer evaluations. A field experiment with 182 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 76 publications
(86 reference statements)
1
27
0
1
Order By: Relevance
“…Since this research is focusing on the female respondents, around 30 females were asked to sniff and evaluate the masculinity/femininity, pleasantness and stimulating nature of the perfumes. The masculinity, femininity, and pleasantness of the scents were rated over a 7-point semantic scale (Douce et al, 2016). The scents were diffused on a paper and handed over to the respondents to rate their responses.…”
Section: Scent Pretestmentioning
confidence: 99%
See 1 more Smart Citation
“…Since this research is focusing on the female respondents, around 30 females were asked to sniff and evaluate the masculinity/femininity, pleasantness and stimulating nature of the perfumes. The masculinity, femininity, and pleasantness of the scents were rated over a 7-point semantic scale (Douce et al, 2016). The scents were diffused on a paper and handed over to the respondents to rate their responses.…”
Section: Scent Pretestmentioning
confidence: 99%
“…On the other hand, incongruent scents may lead to the perceptive intrusion. However, Douce, Janssens, Weralds, and Streukens (2016) suggested that the scent of the opposite sex leads the customer's pleasure and drive for impression management.…”
Section: Introductionmentioning
confidence: 99%
“…To support this model, our work relies on previous literature on general shopping behavior (e.g., Carpenter, ; Stoel et al, ) and on tourist/tourism shopping behavior (e.g., Sirakaya‐Turk et al , ; Yüksel, ), which assume that utilitarian and hedonic values predict customer loyalty. However, as opposed to previous causal approaches stating the simultaneous effects of value dimensions on endogenous variables (e.g., Doucé et al, ; Mathwick et al, , ; Sullivan, Kang, et al , ; Yüksel, ), our model considers a sequence of effects of experiential values (see Figure ). This chain of effects, to the best of our knowledge, has not been proven before.…”
Section: Empirical Study Developmentmentioning
confidence: 99%
“…To bridge this gap, this work has followed recent research calls from tourism researchers (e.g., Choi et al, 2015, p. 12; Sirakaya‐Turk et al, , p. 1882), claiming for more work to be carried out on ETSV. However, in contrast with most previous works that have modeled the simultaneous effects of experiential values on either satisfaction or loyalty (e.g., Doucé et al, ; Carlson et al, ; Gallarza, Arteaga, et al, ; Mathwick et al, , ), our work has posited two research objectives and has (a) tested a structural model with a chain of concatenated effects of experiential values and (b) built a second‐order model as a multidimensional ETSV index. Both models were tested with PLS on a convenience sample of 374 tourists shopping in the city of Valencia (Spain), a prominent shopping and tourism destination in a country with a growing fashion industry, which has a highly internationalized profile (Zara, Mango, Pronovias, and Camper).…”
Section: Conclusion: Contribution Managerial Implications Limitatimentioning
confidence: 99%
See 1 more Smart Citation